2018
DOI: 10.1016/s1470-2045(18)30204-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk-adapted therapy for young children with medulloblastoma (SJYC07): therapeutic and molecular outcomes from a multicentre, phase 2 trial

Abstract: American Lebanese Syrian Associated Charities, St Jude Children's Research Hospital, NCI Cancer Center, Alexander and Margaret Stewart Trust, Sontag Foundation, and American Association for Cancer Research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
193
4
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 171 publications
(217 citation statements)
references
References 33 publications
14
193
4
6
Order By: Relevance
“…Molecular subgroup classifications were included in SJYC07, in which young children with medulloblastoma were prescribed distinct consolidation regimens based off risk group . Risk groups were determined by tumor histology, extent of resection, disease stage, and age.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Molecular subgroup classifications were included in SJYC07, in which young children with medulloblastoma were prescribed distinct consolidation regimens based off risk group . Risk groups were determined by tumor histology, extent of resection, disease stage, and age.…”
Section: Discussionsupporting
confidence: 75%
“…Findings from recently published trials suggest a five‐year progression‐free survival for younger children treated with radiation‐sparing approaching 30 to 60%, compared with 70% for older children . Similarly, overall survival (OS) at five years is 30% to 60% for younger children compared with 60% to 80% for older children …”
Section: Introductionmentioning
confidence: 99%
“…15 Furthermore, new evidence has demonstrated that methylation profiling of infant SHH MB can detect low-risk and high-risk groups within infants in this tumor subgroup. 37,52 Akin to the intertumoral heterogeneity observed within SHH MB, similar observations have been described among group 3 and group 4 MB. Definitively distinguishing group 3 from group 4 MB represents a challenge because of the now accepted inherent molecular overlap between the 2 groups that precludes complete separation.…”
Section: Dna Methylation Profilingsupporting
confidence: 75%
“…) . Furthermore, new evidence has demonstrated that methylation profiling of infant SHH MB can detect low‐risk and high‐risk groups within infants in this tumor subgroup …”
Section: Introductionmentioning
confidence: 99%
“…Only patients enrolled at St. Jude were included in this analysis. The details of this clinical trial, published elsewhere, will be summarized here . Patients enrolled received no systemic prior therapy other than corticosteroids, and upon entry onto the study were stratified into 1 of 3 risk groups (low, intermediate or high) depending on diagnosis, evidence of metastasis, and degree of tumour resection.…”
Section: Methodsmentioning
confidence: 99%